Emergency resections in aneurysms ruptured abdominal aorta, in patients with 80 and over years of age - Lucinschi, Alicia; Matteucci, Pablo (Cirugía del Uruguay, 1991)
Authors present 12 cases of 80 to 94 year old patients who underwent surgical emergency treatment for torn abdominal aorta aneurysms. Al/ cases presented severe hemodynamical repercussion on admission. The aneurysm had been already diagnosed in nine cases, but patients had not been operated on because of their age and risky general condition. Six of the patients died. The other six were discharged from hospital and considered cured. This means the previous 80 year old limit for abdominal aorta aneurysm surgery should no longer be taken into account.